2022
DOI: 10.3389/fpubh.2022.918571
|View full text |Cite
|
Sign up to set email alerts
|

Configurational Paths to Higher Efficiency in County Hospital: Evidence From Qualitative Comparative Analysis

Abstract: BackgroundThe efficient operation of county-level medical institutions is a significant guarantee in constructing Chinese rural tertiary care service networks. However, it is still unclear how to increase the efficiency of county hospitals under the interaction of multiple factors. In this study, 35 county general hospitals in China were selected to explore the configuration paths of county hospitals' high and poor efficiency status under the Environment-Structure-Behavior (ESB) framework and provide evidence-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…Unlike the Luohu Model, technologies, such as Internet Plus, were utilized to facilitate the sharing of diagnosis and treatment information in the Luohu Medical Group, improving medical services’ efficiency ( 65 ). According to the MCs policy, county hospitals play a vital role in ensuring major diseases which can be treated without patients leaving their counties ( 66 ). The above findings suggested that county hospitals should define their positioning and expand their diagnosis coverage by strengthening the comprehensiveness of diagnosis and treatment projects.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike the Luohu Model, technologies, such as Internet Plus, were utilized to facilitate the sharing of diagnosis and treatment information in the Luohu Medical Group, improving medical services’ efficiency ( 65 ). According to the MCs policy, county hospitals play a vital role in ensuring major diseases which can be treated without patients leaving their counties ( 66 ). The above findings suggested that county hospitals should define their positioning and expand their diagnosis coverage by strengthening the comprehensiveness of diagnosis and treatment projects.…”
Section: Discussionmentioning
confidence: 99%
“…Although the central government has prioritized the least developed western region for central financial subsidies, the central developing region has been struggling with limited financial capacities ( 47 ). Rural county hospitals play a pivotal role in the Chinese healthcare system ( 48 ). They not only lead the three-tier healthcare delivery system for rural residents, but also serve as a liaising platform for tertiary hospitals (all metropolitan) to reach rural consumers ( 49 ).…”
Section: Discussionmentioning
confidence: 99%
“…Jing et al (30) evaluated the technical efficiency of public and private hospitals in Beijing, China. After the reform of China's medical system, the public sector have been concerned about the efficiency of primary health services (31)(32)(33)(34), while ignoring the services of hospitals above the second level.…”
Section: Introductionmentioning
confidence: 99%